Enhancing knowledge on low‐value fishing species: the distinct reproductive strategy of two gurnard species. Issue 4 (27th July 2021) - Neves, Ana; Sousa, Inês; Sequeira, Vera; Vieira, Ana Rita; Silva, Elisabete; Silva, Frederica; Duarte, Ana Marta; Mendes, Susana; Ganhão, Rui; Assis, Carlos; Rebelo, Rui; Magalhães, Maria Filomena; et al.
ABSTRACT: The depletion and overexploitation of several fish stock demands for a valorisation of non‐target and discarded species. Nonetheless, such species are often poorly studied, and information on their biological parameters must be gathered for effective population management. For 1 year, the reproductive strategy of the piper gurnard Trigla lyra and the red gurnard Chelidonichthys cuculus was studied by monthly samples obtained from commercial boats operating on western Portuguese coast. Both species showed a biased sex ratio towards females, especially for larger length classes. Length at first maturity could be estimated only for red gurnard (22.1 and 19.9 cm for females and males, respectively) because all piper gurnard individuals caught were mature. Piper gurnard showed determinate fecundity and a short spawning season, from November to February with a peak in January, whereas red gurnard showed indeterminate fecundity and a wide spawning season, from late December to May. The relative annual fecundity estimated for red gurnard (1893 ± 728 oocytes × g −1 eviscerated weight [EW]) was higher than the one estimated for piper gurnard (1018 ± 250 oocytes×g −1 EW). Although important information for understanding the species dynamics is presented in this study, additional information on other life‐history parameters and of species landings is required.